(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Sulphur dioxide (SO₂) is a toxic gas and a major component of air pollution. It interferes with the metabolic and physiological functions of plants, leading to a decline in growth and productivity (Black and Unsworth, 1979). This research was conducted to examine how varying levels of SO₂ (0.1 ppm, 0.2 ppm, 0.4 ppm, and 0.6 ppm) affect the growth of Pisum sativum (pea plants).The findings revealed that the impact of SO₂ exposure depends on its concentration. A minimum reduction in growth was observed at a low concentration (0.1 ppm), while higher levels (0.6 ppm) caused a significant decrease in growth attributes. The study highlights the detrimental effects of SO₂ on plants and underscores the importance of controlling air pollution to safeguard agricultural productivity and plant health.